Challenges and possibilities of Science Education in an inclusive perspective: a case study (Research, Society and Development, 2020)
This study presents the results of an investigation on science teaching in an inclusive perspective from the conceptions of a teacher from the public school system in Alegrete/RS. Therefore, the methodology outlined to achieve the proposed objective was qualitative research, outlined from a case study carried out through a semi-structured interview. The analyzes undertaken corroborate with authors in the area by inferring that initial training, as well as continuing education in Science Education, requires more specific support in relation to the inclusive context. Also, it became evident that the use of didactic resources that are applied to all students promotes a space for social interaction and meaningful learning for students. The participation of families and the collaboration of the AEE professional, when articulated with the teacher of regular education, can favor the implementation of truly inclusive practices.